Development of Isocratic High Performance Liquid Chromatography Method for Simultaneous Analysis of the Flavonol Flavonoids - Crescentiana Emy Dhurhania; Susilowati Susilowati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Quercetin, rutin, and myricetin are flavonoids belonging to the flavonol subclass, commonly found in a variety of fruits, vegetables, and medicinal plants. However, a validated isocratic High Performance Liquid Chromatography (HPLC) method for the simultaneous analysis of these compounds has not yet been established. Therefore, the development of a robust isocratic HPLC method enabling the concurrent quantification of quercetin, rutin, and myricetin within a relatively short analysis time is warranted. The method development process necessitates an initial optimization phase to establish ideal analytical conditions. Therefore, the development of analytical methods in this research begins with the optimization stage aimed at producing ideal conditions during the analysis process. This study commenced with the determination of the optimal detection wavelength for the HPLC detector, followed by the optimization of mobile phase compositions and their respective ratios, as well as the evaluation of acceptance criteria based on column efficiency parameters. The mobile phase consisting of methanol:0.1% phosphoric acid (70:30), at a flow rate of 1 mL/min, produced chromatograms with satisfactory separation. This was evidenced by the resolution factor (R) and the number of theoretical plates (N), both of which met the established acceptance criteria, resolution factor exceeding 1.5 and theoretical plate number above 2000, along with relatively short retention times (Tr). Furthermore, the peak symmetry factors for myricetin and quercetin were within acceptable limits, approaching the ideal value of 1. However, the peak symmetry of rutin requires further refinement to attain an optimal symmetry factor. The mobile phase of methanol:0.1% phosphoric acid (70:30) with a rate of 1 ml/min is most suitable for the simultaneous analysis of quercetin, rutin, and myricetin in the isocratic HPLC method.